MAPK Cascades in Guard Cell Signal Transduction - Lee, Yuree; Kim, Yun Ju; Kim, Myung-Hee; Kwak, June M. (Frontiers in Plant Science, 2016)
Guard cells form stomata on the epidermis and continuously respond to endogenous and environmental stimuli to fine-tune the gas exchange and transpirational water loss, processes which involve mitogen-activated protein kinase (MAPK) cascades. MAPKs form three-tiered kinase cascades with MAPK kinases and MAPK kinase kinases, by which signals are transduced to the target proteins. MAPK cascade genes are highly conserved in all eukaryotes, and they play crucial roles in myriad developmental and physiological processes. MAPK cascades function during biotic and abiotic stress responses by linking extracellular signals received by receptors to cytosolic events and gene expression. In this review, we highlight recent findings and insights into MAPK-mediated guard cell signaling, including the specificity of MAPK cascades and the remaining questions.